ORGANIZATIONAL AND LEGAL FOUNDATIONS OF RELIGIOUS-CONFESSIONAL RELATIONS IN UZBEKISTAN - Karimov Abdumannof Abdujabborovich (The Conference Hub, 2025)
This article examines the organizational and legal foundations of religious-confessional relations in the Republic of Uzbekistan. It analyzes the constitutional principles, legislative frameworks, and institutional mechanisms ensuring freedom of religion and the peaceful coexistence of various religious communities. Special attention is given to the role of state institutions, such as the Committee on Religious Affairs. The article also explores the balance between secularism and the promotion of interfaith dialogue, tolerance, and social stability within a multi-ethnic and multi-confessional society.
Keywords: religious-confessional relations, freedom of conscience, religious organizations, secularism, legislation, tolerance, interfaith dialogue, Committee on Religious Affairs, legal framework.